Assessing student motivation in macroeconomics course during teaching and learning from home / Normala Ismail and Mohamad Kamil Ariff Khalid - Ismail, Normala; Khalid, Mohamad Kamil Ariff (Universiti Teknologi MARA, Pahang, 2022)
The COVID-19 pandemic has adversely affected various sectors including the education sector. According to the UNESCO Monitoring Report there are 192 countries that postponed school and university sessions due to the COVID-19 pandemic. Since the Movement Control Order (MCO) was enforced, the education system in Malaysia has also shifted from traditional classes to Learning and Teaching from Home (LTfH) classes. The transition to this new education system surpassed expectations as it required the involvement and support of various parties, especially lecturers and students. One of the difficulties faced in this transition is to identify the level of students' motivation in the LTfH environment. Thus, this study would like to see the level of students' motivation who take Macroeconomics Course in the LTfH environment. The research instrument was a questionnaire distributed through the Google Forms platform to 113 Diploma in Accountancy students. Findings of the study indicate that students' motivation level is influenced by performance goals, achievement goals, Macroeconomics Course learning values and active learning strategies. It is hoped that this study can help lecturers in planning and compiling online learning strategies in order to contribute to the students' academic success in LTfH.